1998
DOI: 10.1590/s0101-81751998000200013
|View full text |Cite
|
Sign up to set email alerts
|

Panurgillus gênero novo de Panurginae, com a descrição de quatorze espécies do sul do Brasil (hymenoptera, andrenidae)

Abstract: ABSTRACT. PANURGILLUS, A NEW GENUS OF PA NU RGINAE, WITII DESCRIPTI ON OF FOURTEEN SPECI ES FROM S OUTHERN BRA ZIL (HVMENO PTERA, A NDREN IDA E).PanurgilIus, a generic name used by J.S. Moure throughout various years in lill. as a substitue of Panllrginlls in the Neotropical Apifauna, is formally described. Ali specimens of lhe species here described were collecled during surveys of bees and melittophilous plants in th state ofRio Grande do Sul, southem Brazil. Various species of Panurgillus also occur in olhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
1
7
0
2
Order By: Relevance
“…Oligoletia é citada para diversas espécies de Panurginae mas, na maioria, as relações com plantas ainda não são conhecidas. Relações de oligoletia são encontradas em Anthrenoides meridionalis (Schrottky, 1906) com flores de Oxalis (Oxalidaceae) (SCHLINDWEIN 1998;ALVES-DOS-SANTOS 1999), Callonychium petuniae Cure & Wittmann, 1990 com flores de Petunia (Solanaceae) (WITTMANN et al 1990), Arhysosage cactorum Moure, 1999 com flores de Notocactus, Gymnocalycium e Opuntia (Cactaceae) (SCHLINDWEIN & WITTMANN 1995, 1997, Neffapis longilingua Ruz, 1995 com flores de Malesherbia humilis (Malesherbiaceae) (ROZEN & RUZ 1995) e diversas espécies de Panurgillus Moure, 1998 com flores de ervas e arbustos pequenos das famílias Apiaceae, Asteraceae, Malvaceae, Oxalidaceae (SCHLINDWEIN & MOURE 1998;ALVES-DOS-SANTOS 1999a).…”
Section: Discussionunclassified
“…Oligoletia é citada para diversas espécies de Panurginae mas, na maioria, as relações com plantas ainda não são conhecidas. Relações de oligoletia são encontradas em Anthrenoides meridionalis (Schrottky, 1906) com flores de Oxalis (Oxalidaceae) (SCHLINDWEIN 1998;ALVES-DOS-SANTOS 1999), Callonychium petuniae Cure & Wittmann, 1990 com flores de Petunia (Solanaceae) (WITTMANN et al 1990), Arhysosage cactorum Moure, 1999 com flores de Notocactus, Gymnocalycium e Opuntia (Cactaceae) (SCHLINDWEIN & WITTMANN 1995, 1997, Neffapis longilingua Ruz, 1995 com flores de Malesherbia humilis (Malesherbiaceae) (ROZEN & RUZ 1995) e diversas espécies de Panurgillus Moure, 1998 com flores de ervas e arbustos pequenos das famílias Apiaceae, Asteraceae, Malvaceae, Oxalidaceae (SCHLINDWEIN & MOURE 1998;ALVES-DOS-SANTOS 1999a).…”
Section: Discussionunclassified
“…These structures have been used as systematic and taxonomic characters, although their functions are yet unknown. We aimed a morphological analysis at lateral foveae of three species of Panurgillus Moure, 1998: P. vagabundus (Cockerell, 1918, P. reticulatus Schlindwein & Moure, 1998 e P. flavitarsis Schlindwein & Moure, 1998. The study of the external morphology showed that the lateral foveae of the T2 are evident among females, but in males they are undistinguishable or absent.…”
mentioning
confidence: 99%
“…Essas estruturas têm sido usadas como caráter sistemático e taxonômico, entretanto suas funções ainda são desconhecidas. Visamos a análise morfológica das fóveas laterais de três espécies de Panurgillus Moure, 1998: P. vagabundus (Cockerell, 1918), P. reticulatus Schlindwein & Moure, 1998 e P. flavitarsis Schlindwein & Moure, 1998. O estudo da morfologia externa mostrou que as fóveas laterais do T2 são evidentes nas fêmeas, mas inconspícuas ou ausentes nos machos.…”
unclassified
See 2 more Smart Citations